2003
DOI: 10.2118/03-07-02
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Determination of Heavy Oil and Bitumen Using NMR Relaxometry

Abstract: Knowledge of oil viscosity is important when estimating hydrocarbon reserves and evaluating the potential for waterflooding or EOR processes. This information is especially important in heavy oil and bitumen, as viscosity is usually the major impediment to recovery of these reserves. As oil viscosity increases, obtaining a laboratory measurement is difficult and prone to error, and viscosities measured in the lab may not be representative of field conditions. Nuclear magnetic resonance (NMR) is therefore prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 0 publications
1
34
0
1
Order By: Relevance
“…However, as was also demonstrated by Bryan et al [22], the oil phase dependence of the fitting parameters shown in Table 2 requires that oil-specific calibrations would be required to convert T 2gm values to viscosity. Further work has involved the development of NMR viscosity models that relate in-situ oil viscosity to T 2gm and RHI at lower temperatures [48].…”
Section: Measurement Of Oil Relaxation Time In Oil Coresmentioning
confidence: 73%
See 2 more Smart Citations
“…However, as was also demonstrated by Bryan et al [22], the oil phase dependence of the fitting parameters shown in Table 2 requires that oil-specific calibrations would be required to convert T 2gm values to viscosity. Further work has involved the development of NMR viscosity models that relate in-situ oil viscosity to T 2gm and RHI at lower temperatures [48].…”
Section: Measurement Of Oil Relaxation Time In Oil Coresmentioning
confidence: 73%
“…These include investigations into wettability [21], viscosity [22], fluid saturations [23] and emulsions [24]. In the present article, a brief overview of the relevant NMR theory (full details of which can be found in established texts, e g., [25][26][27]) will be followed by an evaluation of the literature, in conjunction with some new experimental results.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory, the fluid sample is placed in a homogeneous magnetic field, so there is also negligible accelerated relaxation due to diffusion in a magnetic field gradient. This means that the measured transverse relaxation is due only to bulk relaxation 38 . Bulk relaxation is a fluid property, and is a measure of how easily the protons give off energy to one another.…”
Section: Spe 86548mentioning
confidence: 99%
“…The scale of distinguishability can reach up to 0.1 mm; and the clarity of images is far more satisfying when compared with CT. NMR has been intensively applied in petroleum research for the past 20 years. These applications include investigation on viscosity, emulsions, wettability, and fluid saturations (Bryan et al, 2003;Hum and Kantzas, 2006;Jiang et al, 2007;Kantzas et al, 2005). Etched-glass micro-model can be used to mimic the pore structures with high distinguishability (Sun and Qu, 2004;Sun and Tang, 2006).…”
Section: Introductionmentioning
confidence: 99%